Implementing Active Learning in the Teaching of Kitab Kuning within the Takhassus Program at Markaz Arabiyah - Anita Firdaus; Rofi'ah, Siti (Journal Of Islamic Education And Pesantren, 2024)
This study aims to analyze the implementation of Active Learning in the teaching of classical Islamic texts (kitab kuning) within the Takhasus Program at Markaz Arabiyah Pare and its implications for pesantren pedagogy. Employing a qualitative field research design, data were collected through observation, interviews, and documentation. The findings reveal that while the epistemic structure of classical texts—such as grammatical analysis (nahwu-sharaf) and the reading of unvocalized texts—remains preserved, instructional strategies are implemented in a participatory manner through small group discussions, student presentations, and the “everyone is a teacher here” technique. This approach encourages students’ intellectual engagement in reading, analyzing, and articulating textual meanings independently. The study demonstrates that the integration of Active Learning does not dismantle the pesantren tradition but revitalizes its pedagogical practices into a more dialogical and constructive model. It highlights the methodological flexibility of pesantren education in adapting student-centered learning approaches while maintaining scholarly authority and ethical values of knowledge transmission.